Protozeolite‐Seeded Synthesis of Single‐Crystalline Hierarchical Zeolites with Facet‐Shaped Mesopores and Their Catalytic Application in Methanol‐to‐Propylene Conversion. Issue 34 (11th July 2022) - Liu, Yinghao; Zhang, Qiang; Li, Junyan; Wang, Xingxing; Terasaki, Osamu; Xu, Jun; Yu, Jihong
Abstract: Hierarchical zeolites integrating intrinsic micropores with secondary meso‐ and/or macropores afford superior catalytic properties for enhanced mass transportation and more accessible active sites. The mesopores generated by using mesoporogens or framework etching are usually irregular with abundant defective sites and low hydrothermal stability. Here, using protozeolite nanoparticles as seeds, we succeeded in the synthesis of single‐crystalline hierarchical ZSM‐5 zeolites with hexagonal mesopores faceted by complete microporous frameworks. The protozeolites played a key role in the formation of faceted mesopores achieved via intraparticle ripening process. Thanks to the unique texture properties and more accessible acid sites at the open location, the as‐prepared zeolites exhibited remarkedly long lifetime (18 h) and high propylene selectivity (52.7 %) with propylene/ethylene ratio of 3.64 in the methanol‐to‐propylene reaction (WHSV=12.5 h −1 ) compared to the counterparts. Abstract : A protozeolite‐seeded synthetic strategy was developed to construct single‐crystalline hierarchical ZSM‐5 zeolites with hexagonal‐shaped mesopores faceted with a complete zeolite microporous framework. The as‐prepared ZSM‐5 zeolites exhibit excellent hydrothermal stability and remarkably improved catalytic performance in the methanol‐to‐propylene reaction compared to traditional hierarchical ZSM‐5 and other related zeolites.